Primary pulmonary Hodgkin’s lymphoma mimicking granulomatosis with polyangiitis – a case report of diagnostic and therapeutic dilemmas - Sławiński, Lucjan; Sołek, Julia Maria; Miłkowska-Dymanowska, Joanna; Jesionek-Kupnicka, Dorota; Góra-Tybor, Joanna; Mikulski, Damian; Braun, Marcin (Contemporary Oncology/Współczesna Onkologia, 2023)
Primary pulmonary Hodgkin’s lymphoma (PPHL) is a rare subtype of lymphoma that comprises a small percentage of primary pulmonary lymphomas. Due to its rarity and nonspecific symptoms, PPHL often presents diagnostic challenges. This case report presents a unique case of PPHL mimicking granulomatosis with polyangiitis, emphasizing the difficulties encountered during the diagnostic process. A 53-year-old female presented with vague symptoms including weakness, oedema, dry cough, and nasal cavity ulceration. Laboratory investigations revealed elevated C-reactive protein levels, a white blood cell count with neutrophilia, and lymphopaenia. Initial treatment with oral corticosteroids for suspected polyangiitis yielded no response. The patient subsequently developed a low-grade fever and pruritic erythematous rash. Diagnostic procedures, including bronchial brush biopsy, bronchial washing, mediastinal lymph node biopsy, nasal cavity ulceration biopsy, and initial lung biopsy, were inconclusive and resulted in exclusion of granulomatosis with polyangiitis. A subsequent computed tomography scan indicated disease progression in the left lung. A lung biopsy revealed fibrotic tissue with nodules containing Hodgkin- Reed-Sternberg cells, leading to the final diagnosis of classic Hodgkin lymphoma, nodular sclerosis subtype. Positron emission tomography scan findings confirmed PPHL. The patient received multiple chemotherapeutic regimens, with brentuximab vedotin demonstrating efficacy as the sole effective treatment. This exceptional case of PPHL underscores the extensive diagnostic and therapeutic workup involving a multidisciplinary team of clinicians, radiologists, and pathologists. Increased awareness of PPHL and its distinctive features will aid in the diagnosis of similar cases in the future, benefitting both clinicians and pathologists.